2022
DOI: 10.3390/electronics11030455
|View full text |Cite
|
Sign up to set email alerts
|

VR-PEER: A Personalized Exer-Game Platform Based on Emotion Recognition

Abstract: Motor rehabilitation exercises require recurrent repetitions to enhance patients’ gestures. However, these repetitive gestures usually decrease the patients’ motivation and stress them. Virtual Reality (VR) exer-games (serious games in general) could be an alternative solution to address the problem. This innovative technology encourages patients to train different gestures with less effort since they are totally immersed in an easy to play exer-game. Despite this evolution, patients, with available exer-games… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…B.Recognition: After data preprocessing, we employed the method proposed in [50] to classify the patient's facial expressions into various emotion categories, including positive, negative, neutral (figure 4). Our previous work [7] involved the use of the combination of MoodMe Emotions Barracuda SDK [49] for pre-processing, and DeepFace [48], for emotion classification, DeepFace a neural network model developed by Facebook's AI Research team in 2014. The recognition module (MoodMe + Deep-Face) has demonstrated its capabilities in our previous research [7].…”
Section: Emotion Recognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…B.Recognition: After data preprocessing, we employed the method proposed in [50] to classify the patient's facial expressions into various emotion categories, including positive, negative, neutral (figure 4). Our previous work [7] involved the use of the combination of MoodMe Emotions Barracuda SDK [49] for pre-processing, and DeepFace [48], for emotion classification, DeepFace a neural network model developed by Facebook's AI Research team in 2014. The recognition module (MoodMe + Deep-Face) has demonstrated its capabilities in our previous research [7].…”
Section: Emotion Recognitionmentioning
confidence: 99%
“…Our previous work [7] involved the use of the combination of MoodMe Emotions Barracuda SDK [49] for pre-processing, and DeepFace [48], for emotion classification, DeepFace a neural network model developed by Facebook's AI Research team in 2014. The recognition module (MoodMe + Deep-Face) has demonstrated its capabilities in our previous research [7]. In this paper, our emphasis is on using emotion recognition to estimate the level of motivation in patients during serious games.…”
Section: Emotion Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Valve Software has actively experimented with biometrics by including them in a special build of Left 4 Dead 2. Valve Software sees affect emotion as a crucial component of future games [15]. In the literature review, several methods used for facial expression detection are identified, and the existing systems are contrasted.…”
Section: Pure Science and Technology Applications (Scug-psta-2022)mentioning
confidence: 99%
“…Granato et al [ 19 ] predicted the subjects’ emotions during video game sessions and indicated that the obtained results could improve the game design. Izountar et al [ 20 ] proposed a VR-PEER adaptive exergame system and developed a virtual reality-based serious game as a case study. The test results showed that fifteen participants expressed the usefulness of the system in motor rehabilitation processes.…”
Section: Introductionmentioning
confidence: 99%